Security Framework for Pervasive Healthcare Architectures Utilizing MPEG-21 IPMP Components - Anastasios Fragopoulos; John Gialelis; Dimitrios Serpanos (International Journal of Telemedicine and Applications)
Nowadays in modern and ubiquitous computing environments, it is imperative more than ever the necessity for deployment of pervasive healthcare architectures into which the patient is the central point surrounded by different types of embedded and small computing devices, which measure sensitive physical indications, interacting with hospitals databases, allowing thus urgent medical response in occurrences of critical situations. Such environments must be developed satisfying the basic security requirements for real-time secure data communication, and protection of sensitive medical data and measurements, data integrity and confidentiality, and protection of the monitored patient's privacy. In this work, we argue that the MPEG-21 Intellectual Property Management and Protection (IPMP) components can be used in order to achieve protection of transmitted medical information and enhance patient's privacy, since there is selective and controlled access to medical data that sent toward the hospital's servers.